การทำยูนิตคอมมิตเมนต์ในระบบไฟฟ้ากำลังขนาดใหญ่ - กมล พงศ์ธาดาพร (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Presents a unit commitment method developed for a large scale power system comprising hydro, fuel constrained thermal and, pond level constrained pumped storage units. With the proposed method, peak loads will be firstly shaved to smooth the hourly load curve by hydro units. Then the rest of the load will be supplied by thermal and pumped storage units, of which the scheduling will be done by an iterative process. Test results based on an actual generating system of the Electricity Generating Authority of Thailand show that the developed method is effective in both the computational time and production cost aspects.